Internet, Telematics and Health - Sosa-Iudicissa, Marcelo (IOS Press, 2014)
This book is the final result of a team effort involving a large number of international experts, coordinated and led by Dr. Marcelo Sosa-Iudicissa, in Brussels, Dr. Nora Oliveri, in Buenos Aires, Dr. Carlos A. Gamboa, in Washington, and Ms. Jean Roberts, in England. They have attracted and assembled together the contributions of 80 specialists from over 20 countries in North America, Europe and Latin America. This makes the present book a unique publication, presenting a true global vision of the opportunities opened up by the advent of the Internet for doctors, health professionals, planners and managers, as well as for patients and the public at large, wanting to know more and better about their own health maintenance and protection. It also presents a range of informatics and telematics applications available nowadays to medicine, examples on how people with a health concern are using the Internet in both industrialised and developing countries. This change, bringing empowerment through knowledge, is showing us the trend towards a New Health Paradigm in the In-formation Society. This book is aimed at medical practitioners, administrators, teachers and students who wish an authoritative state-of-the-art as well as how-to for commencing or enhancing wish done on the Internet. A self-contained CD-Rom is included with the book, providing readers with a flying start in accessing key information sounds.